Designing science presentations : a visual guide to figures, papers, slides, posters, and more - Carter, Matt , 1978- (Elsevier/Academic Press, 2013)
Clear, polished, and stimulating presentations are as important to the scientific profession as they are to business, yet most scientists never receive formal training in the creation, delivery, and evaluation of such material. Compelling science communication is essential for PIs who must publish in high-quality journals, solicit funding, attract lab personnel, and impress colleagues. Likewise, students and post-docs must effectively communicate scientific ideas in order to publish, receive fellowships, network, and advance their careers. In spite of these facts, the scientific publishing market lacks an adequately visual guide to the production of effective presentations. Designing Science Presentations fills that gap and provides visually intensive guidance at every step-from the construction of original figures to the presentation and delivery of those figures in papers, slideshows, posters, and websites. This book provides pragmatic advice on the preparation and delivery of exceptional scientific presentations; demonstrates hundreds of visually striking presentation techniques, giving readers inspiration for creating their own; and is structured so that readers do not need to read from cover to cover to find an answer to a particular question. Clear heading for each section indicates its message, with graphic illustrations to highlight it1-2 summary paragraphs that complement the visual images and clearly discuss the main pointNumerous examples of high-quality figures, page layouts, slides, posters, and web pages to help stimulate readers? ideas for their own presentationsNumerous "before and after" examples so the reader can clearly see the contrast between poor and outstanding presentations